2020
DOI: 10.1111/1346-8138.15666
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after steroid pulse therapy and seasonal effect in acquired idiopathic generalized anhidrosis

Abstract: Acquired idiopathic generalized anhidrosis is a rare disease with unknown etiology. Sudden loss of sweating function adversely affects young patients’ quality of life. Although systemic corticosteroid therapy is the most frequently reported treatment for the disease, its effectiveness is controversial because of the risk of recurrence. To assist clinical decision‐making regarding whether to use steroids, we investigated the treatment responsiveness and recurrence rates in patients undergoing steroid pulse ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Based on the autoimmune mechanism, corticosteroid therapy, and in particular corticosteroid pulse therapy, is recommended as the primary treatment for AIGA [1], although it does not improve all cases. It has been reported that younger age and delay from the onset to the treatment are negative factors for the effectiveness of AIGA treatment [4]. Seasonal factors have a significant effect on both treatment and recurrence for AIGA in Japan [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the autoimmune mechanism, corticosteroid therapy, and in particular corticosteroid pulse therapy, is recommended as the primary treatment for AIGA [1], although it does not improve all cases. It has been reported that younger age and delay from the onset to the treatment are negative factors for the effectiveness of AIGA treatment [4]. Seasonal factors have a significant effect on both treatment and recurrence for AIGA in Japan [4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that younger age and delay from the onset to the treatment are negative factors for the effectiveness of AIGA treatment [4]. Seasonal factors have a significant effect on both treatment and recurrence for AIGA in Japan [4]. The effectiveness of oral administration of cyclosporine and Chinese herbal medicine has been reported in a limited number of the patients [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report stated that the treatment response rate of steroid pulse therapy in 57 patients with AIGA was 73%, and the recurrence rate was 48%. Furthermore, it is interesting that the effectiveness was reduced when the steroid pulse therapy was given in the autumn before it became cold [ 82 ]. A trial of oral immunosuppressants is worthwhile in patients who do not respond to steroid pulse therapy, although only one case is reported in Japan [ 30 ].…”
Section: Management Of and Therapeutic Approach To Cholumentioning
confidence: 99%
“…Although the main symptom of AGAH is heat retention due to decreased perspiration, AIGA is characteristically accompanied by cholinergic urticaria (CholU)‐like rash, stinging dermal pain, or both, triggered by sweating stimuli 1 . Anhidrosis is effectively treated by steroid pulse therapy; 2,3 however, the pain can be intractable in some cases of AIGA 4,5 . The site affected by the rash and pain is not necessarily the same as that of anhidrosis 6 .…”
Section: Introductionmentioning
confidence: 99%